A polymer-coated, paclitaxel-eluting stent (Eluvia) versus a polymer-free, paclitaxel-coated stent (Zilver PTX) for endovascular femoropopliteal intervention (IMPERIAL): a randomised, non-inferiority trial. Issue 10157 (27th October 2018) - Gray, William A; Keirse, Koen; Soga, Yoshimitsu; Benko, Andrew; Babaev, Anvar; Yokoi, Yoshiaki; Schroeder, Henrik; Prem, Jeffery T; Holden, Andrew; Popma, Jeffrey; Jaff, Michael R; Diaz-Cartelle, Juan; et al.
Summary: Background: The clinical effect of a drug-eluting stent in the femoropopliteal segment has not been investigated in a randomised trial with a contemporary comparator. The IMPERIAL study sought to compare the safety and efficacy of the polymer-coated, paclitaxel-eluting Eluvia stent with the polymer-free, paclitaxel-coated Zilver PTX stent for treatment of femoropopliteal artery segment lesions. Methods: In this randomised, single-blind, non-inferiority study, patients with symptomatic lower-limb ischaemia manifesting as claudication (Rutherford category 2, 3, or 4) with atherosclerotic lesions in the native superficial femoral artery or proximal popliteal artery were enrolled at 65 centres in Austria, Belgium, Canada, Germany, Japan, New Zealand, and the USA. Patients were randomly assigned (2:1) with a site-specific, web-based randomisation schedule to receive treatment with Eluvia or Zilver PTX. All patients, site personnel, and investigators were masked to treatment assignment until all patients had completed 12 months of follow-up. The primary efficacy endpoint was primary patency (defined as a peak systolic velocity ratio ≤2·4, without clinically driven target lesion revascularisation or bypass of the target lesion) and the primary safety endpoint was major adverse events (ie, all causes of death through 1 month, major amputation of target limb through 12 months, and target lesion revascularisation through 12 months). We set a non-inferiority margin of −10% at 12 months. Primary non-inferiority analyses were done when the minimum sample size required for adequate statistical power had completed 12 months of follow-up. The primary safety non-inferiority analysis included all patients who had completed 12 months of follow-up or had a major adverse event through 12 months. This trial is registered with ClinicalTrials.gov, number NCT02574481 . Findings: Between Dec 2, 2015, and Feb 15, 2017, 465 patients were randomly assigned to Eluvia (n=309) or to Zilver PTX (n=156). Non-inferiority was shown for both efficacy and safety endpoints at 12 months: primary patency was 86·8% (231/266) in the Eluvia group and 81·5% (106/130) in the Zilver PTX group (difference 5·3% [one-sided lower bound of 95% CI −0·66]; p<0·0001). 259 (94·9%) of 273 patients in the Eluvia group and 121 (91·0%) of 133 patients in the Zilver PTX group had not had a major adverse event at 12 months (difference 3·9% [one-sided lower bound of 95% CI −0·46]; p<0.0001). No deaths were reported in either group. One patient in the Eluvia group had a major amputation and 13 patients in each group required target lesion revascularisation. Interpretation: The Eluvia stent was non-inferior to the Zilver PTX stent in terms of primary patency and major adverse events at 12 months after treatment of patients for femoropopliteal peripheral artery disease. Funding: Boston Scientific.